Dementia diagnosis and management: a narrative review of changing practice - Koch, Tamar (Royal College of General Practitioners, 2011)
BACKGROUND: Early detection and management of dementia in primary care are difficult problems for practitioners. England's National Dementia Strategy 2009 seeks to improve these areas but there is limited evidence on how to achieve this most effectively. AIM: This review aims to identify and appraise empirical studies of interventions designed to improve the performance of primary care practitioners in these areas. DESIGN: A narrative review of primary-care based studies. METHOD: Publications up to February 2010 were identified by searching the electronic databases MEDLINE, Embase, and PsycINFO, and bibliographies. The criterion for inclusion was that studies had to be of interventions aimed at improving detection or management of dementia in primary care. Exclusion criteria included studies in non-English publications, pharmacological interventions, and screening instrument studies. Quality was assessed using the PEDro (Physiotherapy Evidence Database) scale. RESULTS: Fifteen studies were identified, of which 11 were randomised controlled trials. Eight reported educational interventions, and seven trialled service redesign, either by changing the service pathway or by introducing case management. Educationally, only facilitated sessions and decision-support software improved GPs' diagnosis of dementia, as did trials of service-pathway modification. Some of the case-management trials showed improved stakeholder satisfaction, decreased symptoms, and care that was more concordant with guidelines. CONCLUSION: The quality of the studies varied considerably. Educational interventions are effective when learners are able to set their own educational agenda. Although modifying the service pathway and using case management can assist in several aspects of dementia care, these would require the provision of extra resources, and their value is yet to be tested in different health systems.